My mom is not interested: a case study of a daughter and her intellectually disabled mother - Joubert, Susan (Department of Psychology, 2015)
"Intimate attachments to other human beings are the hub around which a person's life revolves, not only when (she) is an infant or a toddler or a schoolchild but throughout (her) adolescence and (her) years of maturity as well, and into old age" (Bowlby 1980, p. 422). The attachment literature is a growing area of interest, with renewed focus pioneered by Bowlby. In the South African context attachments to primary caregivers have been under siege of the apartheid group areas act, migrant labour, endemic poverty, widespread HIV/Aids and ongoing political uncertainty. As disorganised attachments in early life result in complex relational disturbance, this research paper commences with a detailed review of the literature on disorganised attachment. It describes the intergenerational transmission of disorganised attachment in one particular case. The research concludes with a reflection on the challenges of interventions in cases of this kind, where resources are limited and work is complex and intransigent.